Female preponderance in genetic generalized epilepsies - Videira, Gonçalo (2021)
Introduction: Epilepsy is more prevalent in men but Genetic Generalized Epilepsies (GGE) seem to be more common in women. A predominant maternal inheritance has been previously described in GGE. Our objective was to determine sex and inheritance patterns in a GGE population compared to mesial temporal lobe epilepsy with hippocampal sclerosis (MTLEHS). Methods: We performed a prospective observational study including adult GGE and MTLEHS patients followed up at a tertiary epilepsy center from January 2016 to December 2019. Patients' familial history was obtained by a detailed questionnaire. Clinical and demographic data was retrieved from clinical notes. Results: A cohort of 641 patients, 403 with GGE and 238 with MTLEHS, was analyzed. GGE was more common in women than MTLEHS (58.8% vs 44.5%, OR=1.63, p = 0.004). Compared to MTLEHS patients, more GGE patients had familial history of epilepsy (45.4% vs 25.2%; p<0.001). The GGE group had a higher percentage of female relatives with epilepsy (55% vs 37%; p = 0.006). The prevalence of maternal inheritance was not different between GGE and MTLEHS groups (62.9% vs 57.7%; p = 0.596). Photosensitivity was more common in females than in males (44.7% vs 34.3%, p = 0.036). Conclusion: There is a female preponderance in GGE when compared to MTLEHS, as both GGE patients and their affected relatives are more frequently women. The prevalence of maternal inheritance was not higher in GGE than in MTLEHS.